2013
DOI: 10.3171/2013.3.jns122114
|View full text |Cite
|
Sign up to set email alerts
|

Society of Neurological Surgeons boot camp courses: knowledge retention and relevance of hands-on learning after 6 months of postgraduate year 1 training

Abstract: Object In July 2010, the Society of Neurological Surgeons (SNS) introduced regional courses to promote patient safety and teach fundamental skills and knowledge to all postgraduate Year 1 (PGY1) trainees entering Accreditation Council for Graduate Medical Education (ACGME)–accredited US neurosurgery residency programs. Data from these courses demonstrated significant didactic learning and high faculty and resident satisfaction with hands-on training. Here, the authors evaluated the durability of learning from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…This has not been extensively examined in otolaryngology, with the exception of a study that looked specifically at the outcomes of head and neck cancer patients, which also showed a lack of a July effect . Rather, novice trainees can be anxious about their new role as first responders and may lack confidence in their management knowledge and skills . A recent study in pediatrics demonstrated an increased reporting of medical errors by new interns in the month of July in a hospital‐wide database despite a lack of increased adverse events in patient outcomes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has not been extensively examined in otolaryngology, with the exception of a study that looked specifically at the outcomes of head and neck cancer patients, which also showed a lack of a July effect . Rather, novice trainees can be anxious about their new role as first responders and may lack confidence in their management knowledge and skills . A recent study in pediatrics demonstrated an increased reporting of medical errors by new interns in the month of July in a hospital‐wide database despite a lack of increased adverse events in patient outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…A number of medical and surgical specialties have invested in developing regional boot camps with standardized curricula to ensure broad availability and a uniform experience for their trainees . Some report near 100% participation, with an overwhelmingly positive response by both residents and faculty who participated in the courses …”
Section: Introductionmentioning
confidence: 99%
“…12 . Surveys conducted in neurosurgery found a high -level of satisfaction and knowledge retention of the skills that were emphasized at the neurosurgical boot camp.…”
Section: Initial Use Of Simulation In Neurosurgery Residencymentioning
confidence: 99%
“…Surveys conducted in neurosurgery found a high -level of satisfaction and knowledge retention of the skills that were emphasized at the neurosurgical boot camp. 12 Appropriate simulators found at postgraduate year one training events have included central line placement, ventriculostomy catheter placement, and trauma craniotomy models.…”
Section: Initial Use Of Simulation In Neurosurgery Residencymentioning
confidence: 99%
“…Now his concept has expanded significantly to the benefit of all! 15 Similarly, Bob Harbaugh and Tony Asher have been early innova tors in the realm of registries to promote quality outcomes research. Their brainchild, NeuroPoint Alliance (NPA), now serves as a model for specialty collaboration in as sessing and promoting quality outcomes.…”
Section: Department Of Neurosurgery College Of Physicians and Surgeomentioning
confidence: 99%